Program of learning strategies for students of an educational institution - Dorado, Alvaro; Ascuntar, Jairo; Garces, Yamile; Obando, Lina (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Nowadays educational institutions, within the school curricula, look for both adopting and applying learning strategies that allow for the strengthening of training of students, who are sought to be reflective and critical towards their learning process. That is why the objective of this study is the implementation of a program of learning strategies for students of an educational institution in Sibundoy, Putumayo. The research was carried out from the qualitative paradigm, with a social critical approach and an action research method. The sample was composed of 90 students of eighth, ninth, and tenth grades. For information gathering, the semi-structured interview and the focus group were used. One of the main findings was a diagnosis by which the population was characterized. In addition, the guidelines for the development of the learning strategies program emerged, among which affective-emotional ones and those of repetition, regulation, elaboration and organization were found. It is concluded that learning strategies gain great importance in the academic context since through them students adopt a critical position towards their own learning process.